Bridging innovation, nature and tradition: assessment of strategies for rural tourism development in Maramureş (Romania) - Regoli, Francesca <1975> (Alma Mater Studiorum - Università di Bologna, 2011)

(untitled)
In the frame of EU rural policy, always more oriented towards environmental concerns and green livelihoods, Romania stands out for the predominance of rural areas and high nature value farming. The country has to face the challenge of joining the modernization process of rural farming systems with the valorization of local assets. Tourism has emerged as one of the main drivers of change and contributors for a sustainable exploitation of local resources. Rural tourism (RT) can foster the enhancement of the territorial capital (TC), the preservation of public goods (PGs) and the promotion of a more environmental oriented livelihood. The research focuses on a case study area, two valleys from Maramureş, where environmental approaches as diversification strategies are partially explored. The work investigates the role of tourism initiatives for the promotion of green oriented practices. The first part of the work is based on a literature review and interdisciplinary analysis of secondary data to identify the key issues: from rural development policy, to the concept of TC, of PGs and RT. The Romanian development programmes and related strategies are investigated; afterwards the characteristics of the County and the role of RT as diversification and valorisation policies is considered. The second part is based on the collection of primary data through interviews to different local stakeholders (farmers owners of rural guesthouses, local administrators, networks and artisans). The main frequencies are analyzed, a cluster analysis is computed to evaluate the similarities within the most representative groups and a comparative analysis is carried out between the two Valleys. The frame of the analysis is based on a set of indicators following the dimensions of the TC, to assess the characteristics of the local stakeholders and to outline the perception about the local PGs and on the adopted strategies to manage the territory. Final considerations are elaborated and few scenarios are outlined, giving relevance to the importance of improving awareness and creating embeddedness among public-private local stakeholders and resources as a tool for a socio-economic and environmental development of the area.